Odpowiedź:
a)
[tex]\frac{3}{4}-\frac{1}{7}=\frac{21}{28}-\frac{4}{28}=\frac{17}{28}[/tex]
[tex]\frac{7}{10}-\frac{4}{15}=\frac{21}{30}-\frac{8}{30}=\frac{13}{30}[/tex]
[tex]\frac{3}{14}-\frac{1}{5}=\frac{15}{70}-\frac{14}{70}=\frac{1}{70}[/tex]
b)
[tex]2\frac{3}{5}-\frac{7}{10}=2\frac{6}{10}-\frac{7}{10}=1\frac{16}{10}-\frac{7}{10}=1\frac{9}{10}[/tex]
[tex]2\frac{3}{8}-1\frac{5}{6}=2\frac{9}{24}-1\frac{20}{24}=1\frac{33}{24}-1\frac{20}{24}=\frac{13}{24}[/tex]
[tex]3\frac{1}{6}-2\frac{3}{4}=3\frac{2}{12}-2\frac{9}{12}=2\frac{14}{12}-2\frac{9}{12}=\frac{5}{12}[/tex]
Szczegółowe wyjaśnienie: